2016
DOI: 10.1007/s40291-016-0234-z
|View full text |Cite
|
Sign up to set email alerts
|

An Eye on Age-Related Macular Degeneration: The Role of MicroRNAs in Disease Pathology

Abstract: Age-related macular degeneration (AMD) is the primary cause of blindness in developed countries, and is the third leading cause worldwide. Emerging evidence suggests that beside environmental and genetic factors, epigenetic mechanisms, such as microRNA (miRNA) regulation of gene expression, are relevant to AMD providing an exciting new avenue for research and therapy. MiRNAs are short, non-coding RNAs thought to be imperative for coping with cellular stress. Numerous studies have analyzed miRNA dysregulation i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
84
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 110 publications
2
84
1
Order By: Relevance
“…Because miR-155 is associated to blood brain barrier dysfunction (Lopez-Ramirez et al, 2014), the up-regulation of miR-155 in retina of rats injected with Aβ oligomers might also influence the integrity of blood retinal barrier (BRB). MiR-155 and its angiogenic target gene CCN1 were found to alter vascular and neovascular growth in mice retina (Berber et al, 2017). Increased expression of miR-155 induced formation of neovascular tufts that growth abnormally in vitreous with concomitant retinal microglial activation (Yan et al, 2015); thus, up-regulation of miR-155 in retina of Aβ injected rats might be the triggering factor of retinal inflammation and pro-angiogenic events.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because miR-155 is associated to blood brain barrier dysfunction (Lopez-Ramirez et al, 2014), the up-regulation of miR-155 in retina of rats injected with Aβ oligomers might also influence the integrity of blood retinal barrier (BRB). MiR-155 and its angiogenic target gene CCN1 were found to alter vascular and neovascular growth in mice retina (Berber et al, 2017). Increased expression of miR-155 induced formation of neovascular tufts that growth abnormally in vitreous with concomitant retinal microglial activation (Yan et al, 2015); thus, up-regulation of miR-155 in retina of Aβ injected rats might be the triggering factor of retinal inflammation and pro-angiogenic events.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, identification and validation of serum, minimally-invasive, biomarkers of AMD are still challenging. In this perspective, differential expression of miRNAs in serum or plasma represents a potential approach to identify novel biomarkers and pharmacological targets of AMD as suggested by Berber et al in their compelling review (Berber et al, 2017). MiRNAs are short, approximately 22-mer, non-coding RNA molecules bearing important regulatory functions, such as post-transcriptional regulation of gene expression (Bartel, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has identified as many as 416 miRNAs which are expressed in RPE and choroid . Targeting these miRNAs in order to modulate their expression seems to be a promising strategy in AMD treatment as supported by experiments conducted in animal models of AMD …”
Section: Introductionmentioning
confidence: 98%
“…MicroRNAs (miRNAs) are a class of small, noncoding RNAs that negatively regulate gene expression posttranscriptionally by partial or full complementary matching with the 39-UTR of target mRNAs (14). Recent studies in animals and humans have revealed important functions of miRNAs in the development and progression of wet AMD (15)(16)(17). Thus far, several miRNAs with proangiogenic (miR- 23, -27, and -155) or antiangiogenic (miR-31, -150, -24, -29, and -93) functions have been identified by using the laser-induced CNV murine model, a wellestablished model that closely mimics the pathogenesis of AMD in humans (18)(19)(20)(21)(22)(23)(24); however, it remains unclear whether other miRNAs, especially those that target to CXCR7, are also involved in the process of angiogenesis in CNV.…”
mentioning
confidence: 99%